f(x) = x^3 +x^2 -2x

First we will calculate the derivative of f(x)

f'(x) = 3x^2 + 2x -2

Now we will substitute with x=1

f'(1) = 3+2-2 = 3

Now we will substitute with x=-1

f'(-1) = 3-2-2= -1

Then f'(1) + f'(-1)= 3 + -1= 2

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now